(untitled) (Third Sector Social Economic Review, 2020)
Due to the increasing global competition, many companies had to radically change their production methods to increase their competitiveness. In order to compete and reach the goal of being the best in this mass competition, they adopted a number of advanced tecniques such as Just-in-time production, total quality management, lean production, flexible produciton systems, process improvement etc. The purpose of all these techniques is to reduce cost, improve quality and increase flexibility in production. These radical changes in production techniques were later reflected in financing techniques and cost management systems. The aim of this study is to reduce costs and provide efficiency in costs by using kaizen costing method in a textile company producing jeans. In this context, face-to-face interviews and on-site inspections were carried out with company managers in a textile company operating in Kahramanmaraş. Based on the findings obtained from the data of the company in 2019, how much cost should be reduced by the kaizen costing method of the company, and what rate and what costs should be reduced in order to reach the target profit margin for 2020.